Pemberdayaan Perempuan di Sektor Pariwisata dalam Perspektif Ekofeminisme - Aulia Rahmawati; Rudi Saprudin Darwis (Politeknik Kesejahteraan Sosial Bandung, 2023)
The topic of women in the tourism sector has been extensively researched. However, there have been few studies that attempt to examine the involvement of women in tourism from an ecofeminist perspective. Yet, women and the environment are primary issues in ecofeminist discourse. Therefore, this article will discuss the empowerment of women in the tourism sector from an ecofeminist perspective. In addition to enriching the study of women and tourism, this article also aims to highlight the importance of empowering women to achieve sustainable tourism. The research is conducted using a literature review method. The results show that the empowerment of women can lead to increased income, a sense of pride in where they live, opportunities for involvement and decision-making, as well as good relationships within their groups. These results will also indirectly bring the community closer to the creation of sustainable tourism.